2020
DOI: 10.1055/s-0040-1713810
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Posterior Cruciate Ligament Resection on Tibiofemoral Joint Gap in Varus Osteoarthritic Knees

Abstract: Posterior cruciate ligament (PCL) resection during posterior-stabilized total knee arthroplasty (PS-TKA) has been reported to preferentially increase the tibiofemoral joint gap in flexion compared with extension. However, previous assessments of the joint gaps have been performed after bone resection and medial soft tissue release. Thus, these procedural steps may have the potential to influence soft tissue balance. In native knees, soft tissue laxity is generally greater in the lateral compartment than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Other studies have indicated that PCL resection does not affect the flexion gap in PS TKA or cause a flexion–extension gap mismatch [ 17 , 18 , 19 ]; Burkhart et al and Oshima et al reported that MCL release causes flexion gap changes but not PCL resection under a similar distraction force to that used in the current study [ 20 , 21 ]. Unfortunately, the study by Burkhart et al was a cadaveric study that was different from the soft tissue in vivo, which may explain the difference between the results [ 20 ].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Other studies have indicated that PCL resection does not affect the flexion gap in PS TKA or cause a flexion–extension gap mismatch [ 17 , 18 , 19 ]; Burkhart et al and Oshima et al reported that MCL release causes flexion gap changes but not PCL resection under a similar distraction force to that used in the current study [ 20 , 21 ]. Unfortunately, the study by Burkhart et al was a cadaveric study that was different from the soft tissue in vivo, which may explain the difference between the results [ 20 ].…”
Section: Discussionmentioning
confidence: 49%
“…In their in vivo study, Oshima et al proposed results inconsistent with our findings. Differing from this study, they performed a pretest before bone resection and measured the gaps while the patella was laterally displaced, rather than in a neutral position, which may also have affected their results [ 21 ]. In addition, the femoral insertion of the PCL had two bundles [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior cruciate ligament (PCL) plays a very important role in knee kinematics, functional recovery, and prosthesis survival after PCL-retaining total knee arthroplasty (CR-TKA). An intact or well-preserved PCL in TKA can effectively reproduce physiological kinematics such as femur rollback (1), lateral pivot at early flexion, and medial pivot at mild flexion (2). Furthermore, a wellpreserved PCL can help restore daily movement, such as walking and climbing stairs, after TKA (3).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a wellpreserved PCL can help restore daily movement, such as walking and climbing stairs, after TKA (3). However, there is no consensus regarding the effects of the PCL on softtissue balance in the knee (2,(4)(5)(6)(7)(8)(9)(10)(11). While some studies have reported that PCL release selectively increases the flexion gap more than the extension gap and accordingly causes a mismatch of the extension and flexion gaps, other studies have not confirmed these results (2,10).…”
Section: Introductionmentioning
confidence: 99%